Therapeutic effect of Lactobacillus rhamnosus SHA113 on intestinal infection by multi-drug-resistant Staphylococcus aureus and its underlying mechanisms. Issue 7 (26th June 2020) - Liu, Guanwen; Pang, Bing; Li, Na; Jin, Han; Li, Junjun; Wu, Wanqin; Ai, Chongyang; Jiang, Chunmei; Shi, Junling
Abstract : Lactobacillus rhamnosus SHA113 showed therapic effects on the instestinal infection caused by Staphylococcus aureus, especially multi-drug-resistant (MDR) pathogenic S. aureus . Abstract : Staphylococcus aureus, especially multi-drug-resistant (MDR) pathogenic S. aureus, poses a severe threat to food safety and human health. Probiotics offer promising potential for the control of MDR pathogens because of their safe and biofunctional properties. This study shows that Lactobacillus rhamnosus SHA113, a strain isolated from the milk of healthy women, could efficiently inhibit MDR S. aureus both in vitro and in vivo . In vitro, L. rhamnosus efficiently inhibited and even killed drug resistant and drug sensitive S. aureus strains . In vivo experiments showed that SHA113 could efficiently decrease the number of S. aureus cells, inhibit the expression of inflammatory factors TNF-α and IL-6, and restore the level of white cells and neutrophils in the blood. SHA113 could also efficiently repair damage of the intestinal barrier and other functions impaired by S. aureus infection. This was indicated by a change of intestinal villi length and structure, and an up-regulated expression of tight junction proteins ZO-1 and occludin. SHA113 also restored the structural damage of immune organs, such as the enlargement of the spleen and the increased level of inflammatory cytokines caused by S. aureus infection. More importantly, L. rhamnosus SHA113 showed more effective inhibitory and therapeutic effects on MDR S. aureus strain ZBQ006 than on drug sensitive S. aureus strain 29213. These results illustrated that L. rhamnosus SHA113 has great potential for the treatment of MDR S. aureus contamination as food control and for therapeutic treatment.